2013
DOI: 10.1002/met.1376
|View full text |Cite
|
Sign up to set email alerts
|

Predicting giant panda habitat with climate data and calculated habitat suitability index (HSI) map

Abstract: ABSTRACT:Climate data are particularly important in Species Distribution Models (SDMs) that are used for predicting global warming consequences on plant and animal distributions. A number of the plants and animals, especially the endangered species such as the giant panda (Ailuropoda melanolecua), are limited in their scope of distribution due to climate changes. Thus, predicting the habitat quality distribution under climate change is important for protecting these species. In this paper the existing and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Other recent studies of the entire giant panda distribution area showed that 53-71% of the current habitats would be lost under the climate scenarios. They predict that future suitable habitats would likely be located in high-elevation areas in the Min Shan and Liang Shan (Li et al, 2015), and the suitable habitat gradually moves north under projected global climate change (Jian et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies of the entire giant panda distribution area showed that 53-71% of the current habitats would be lost under the climate scenarios. They predict that future suitable habitats would likely be located in high-elevation areas in the Min Shan and Liang Shan (Li et al, 2015), and the suitable habitat gradually moves north under projected global climate change (Jian et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the quality of the habitat of giant pandas in the existing and potential habitats of the giant pandas, excepting the Qinling mountains, gradually turns worse with climate change (a decrease of 3.16%) (Jian et al. ). It can be deduced that the impacts of climate change on giant pandas in north Minshan mountains is not too bad as expected for the following two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Giant panda habitats are characterized by high mountains and deep valleys, and complex physical (e.g., soil type) conditions (Viña et al, 2010), where small‐scale topographic features such as slopes and ephemeral waterways play a major role in the microenvironment (Ehleringer & Cooper, 1988). Increased precipitation would alter this microenvironment, such as soil biota, increasing erosion and streamflow, and plant and animal diversity (Bhalla et al 2021; Blankinship et al, 2011; Eisenhauer et al, 2012; Engelbrecht et al, 2007), resulting in a degradation of giant panda habitat (Jian et al, 2014). Higher precipitation and erosion increase soil instability of the microenvironment, causing geo‐hazards and potentially increasing panda injuries and death.…”
Section: Discussionmentioning
confidence: 99%